2013
DOI: 10.1002/rcs.1518
|View full text |Cite
|
Sign up to set email alerts
|

Robotic surgery for deep endometriosis: a paradigm shift

Abstract: This series of robotic procedures for DIE represents the largest currently available and it helps to promote robotics as a safe and attractive alternative to accomplish a comprehensive surgical treatment of DIE, especially when bowel or bladder resections are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 25 publications
0
42
1
1
Order By: Relevance
“…This study demonstrates that robotic resection of DIE is a viable approach for comprehensive surgical management of DIE with comparable symptom resolution. Due to the mechanical and ergonomic advantages of robotic‐assisted surgery and newer data showing similar outcomes to laparoscopy, surgeons treating DIE have started to migrate toward a robotic platform …”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates that robotic resection of DIE is a viable approach for comprehensive surgical management of DIE with comparable symptom resolution. Due to the mechanical and ergonomic advantages of robotic‐assisted surgery and newer data showing similar outcomes to laparoscopy, surgeons treating DIE have started to migrate toward a robotic platform …”
Section: Discussionmentioning
confidence: 99%
“…Deep infiltrating endometriosis is one of the most suitable indications for robotic surgery in benign gynecological disease treatment. Since the patients are still young and wish to have children, they require organ-preserving and tissue-protective surgery (13). Continuity is usually preserved during excision of the endometriosis from the rectum and the ureter.…”
Section: Application In Benign Gynecological Diseasesmentioning
confidence: 99%
“…However, more extensive interventions with partial resection of the bowel or bladder can also be performed with lower complication rates by this minimally invasive approach. Furthermore, the excellent view and the precise navigation of instruments permit preservation of the ovarian reserve, optimal restoration of anatomical conditions, and the prevention of postoperative adhesions (13). Recent investigations have shown that robotic surgery achieves these goals in the vast majority of cases, such as the fulfillment of a woman's wish for children, a significant reduction of pain, and the improvement of gastrointestinal symptoms.…”
Section: Application In Benign Gynecological Diseasesmentioning
confidence: 99%
“…Robot-assisted approaches had reportedly been used for endometriosis surgery [47], Siesto in the largest series published regarding robot-assisted surgery for deep infiltrating endometriosis concluded robot-assisted surgery is a safe and attractive alternative to accomplish a comprehensive surgical treatment especially when bowel or bladder resections are required [48].…”
Section: General Gynecology: Endometriosis Surgerymentioning
confidence: 99%